Influence and Impact of Indian Buddhism on Vietnamese Buddhist History During the 1st to 14th century A.D. - Chi Luc, Ven. Le (Journal of Dhamma for Life, 2022)
The study is “Influence and Impact of Indian Buddhism on Vietnamese Buddhist History During the 1st to 14th century A.D.”. It comes to the last state. The research objectives devices into three main themes as follows (1) to study the history links between Indian Buddhism and Vietnamese Buddhist, (2) to study Art and structural of Indian Buddhism towards Vietnamese Buddhist, (3) to analysis the influences and impacts of Indian Buddhism on the Vietnamese Buddhist historical. Indian monks brought Buddhism, scriptures, Buddha statues and other forms of Indian worshiped to Vietnam through international trade, because of that is indigenous people deeply influenced by foreign culture especially in terms of arts. Some of the Buddha statues have been found to be influenced by Indian schools of arts or originated from India school of arts, such as Amaravati, Gandhara, and Dvaravati. By archaeologist’s findings, we can unveil the curtain of history to see that Buddhist thought and practice has grown very strongly and originated directly from India. The study finds the influences and impacts of Indian Buddhism on Vietnamese Buddhist society based on historical as (1) Influences and impacts on Buddhist literary and scripture, (2) Influences and impacts on Nation Buddhist tradition and culture, (3) Influences and impacts on Education (4) Influences and impacts on Policy and National security, (5) Influences and impacts on Art and Architecture, (6) Influences and impacts on folk life and idea, and (7) Influences and impacts on developing mind and behavior. There are leads to discuss and present truth feature of Vietnamese Buddhist in the ancient time on 1st – 14th centuries A.D.